TEST APPLICATION OF LIQUID ORGANIC FERTILIZER DOSE FROM AGRICULTURAL WASTE ON CUCUMBER PLANTS (Cucumis Sativus L) - Rangga Kusumah; Adrianus Adrianus; Amelia A. Limbongan (Musamus Journal of Agrotechnology Research, 2018)
The efficiency of fertilizer use is now a necessity in the management of farming in Indonesia. farmers dependents on anorganic fertilizer in the long term will results in soil and ecological damage. This research aims to find the efectivity of liquid organic fertilizer in different aplication doses on growth and production of cucumber plants. This study was conducted in Kampung Yasa Mulya, district of slope of Merauke regency. The design used in the study was a randomized design of a group with five treatments and three repeats. On the vegetative observation the treatment effect the secondary branch, but had no effect on the length of the main branch. In generative parameters, the treatment showed significant effect on the amount of potential flower, fruit diameter and fruit weight. The best results are demonstrated by D3 treatment on of the number of secondary branch with an average of 3.93 branch, and D4 treatment on observations of potential flowers rates with an average of 6.73 flower, the number of harvest fruits 16, the fruit length with an average of 16.63 cm, The diameter of the fruit with an average of 3.6 cm and on the observation of the fruit weights with an average of 296,5 g. Keywords: Liquid organic fertilizer; growth; cucumber